STRUCTURA CONTULUI DE PROFIT ŞI PIERDERE – ÎNTRE REGULI CONTABILE ŞI STANDARDE - Florin Radu; Gabriela Daniela Olaru (EIRP Proceedings, 2006)
The profit and loss account is the synthesis document that offers the information concerning the enterprise performances, through the flows that determine the result seen as variation of equity capitals during a financial year, that is, it indicates the degree in which the enterprise achieved the objective in obtaining the profit. Taking into account the different meanings of the term “performance”, it can be defined by the accounting information users in accordance with their own interests.